Fundamental frequency switching strategies of a seven level hybrid cascaded H-bridge multilevel inverter - Chenchireddy, Kalagotla; Sreejyothi, Khammampati R.; Ganesh, Podishetti; Kiran, Gatla Uday; Shiva, Chilukuri; Kumar, Banoth Nithish (International Journal of Applied Power Engineering (IJAPE), 2024)
This paper presents a novel hybrid cascaded H-bridge multilevel inverter (HCHB MLI) designed to address the growing importance of multilevel inverters in the context of renewable energy sources such as solar, wind, and fuel cells. The proposed topology features eight insulated-gate bipolar transistor (IGBT) switches and utilizes two distinct input direct current (DC) sources: a battery and a capacitor, making it a hybrid system. The control strategy employed in this topology is based on fundamental switching frequency techniques. Simulation results of the proposed topology are conducted using MATLAB/Simulink software, while hardware experimentation with a single-phase H-bridge inverter is also demonstrated in the paper. For pulse generation and IGBT switch control, an Arduino UNO microcontroller is utilized. The output voltage of the single-phase H-bridge inverter is verified through experimentation using a cathode-ray oscilloscope (CRO).